Analysis of Students’ Motivation and Ability in Writing Essay - Andi Patmasari; Agussatriana; Kamaruddin, Abdul; Putri, Dwi (Ethical Lingua: Journal of Language Teaching and Literature, 2023)
This research aimed to find out the students’ motivation and ability in writing essay. Investigation and analysis related to motivation and ability of students in writing will be used as consideration in determining the learning method or model applied in writing class. This research used descriptive qualitative research. The data sources or respondents in this research were students of English Education Study Program at Tadulako University who joined the Writing in Professional Context course. The instruments used were writing proficiency test, questionnaire, and interview. The results of data analysis showed that the students’ motivation in writing essay is very strong. In addition, the students’ ability to write essay, especially in terms of five aspects, namely content, organization, vocabulary, language use, and mechanics is quite good.